"It's hip to be square": Grounding moral traits in geometric shapes. (2nd July 2019) - Ke, Yannan; Zhang, Yan; Jiang, Jiang; Xu, Yan
Abstract : To examine the hypothesis that there is a metaphoric link between geometric shapes (square vs. circle) and moral traits (integrity vs. deviousness), we conducted three experiments in China. In Study 1, integrity‐related words were classified faster when embedded in a square than in a circle. Conversely, deviousness‐related words were classified faster in a circle than in a square. Study 2 found that a person who preferred squares was perceived as more righteous and that a person who preferred circles was perceived as more devious. Study 3 revealed that the participants were more likely to pair a square with integrity‐related words and a circle with deviousness‐related words in a memory task. Given the negation of square‐integrity and circle‐deviousness emotional congruence, the findings of this research show that shape‐related information is a meaningful part of the mental representations of moral traits.